The Nature of Law Enforcement against Drug Abusers in the South Sulawesi Police Jurisdiction - Isvany, Andi Lulu (Journal of Cultural Analysis and Social Change, 2026)
This study examines the essence and effectiveness of law enforcement against narcotics abuse offenders within the jurisdiction of the South Sulawesi Regional Police (Polda Sulawesi Selatan). Narcotics crimes in Indonesia have transformed into complex, transnational, and technologically driven criminal networks that demand extraordinary legal responses. Although Law No. 35/2009 on Narcotics provides broad investigative authority—including wiretapping, undercover buy operations, and controlled delivery—the practical implementation of these provisions faces substantial structural, technical, and cultural barriers. Using a juridical-empirical approach and the systems theory of Lawrence M. Friedman, this research explores how legal structure, substance, and legal culture interact in shaping enforcement outcomes. The findings reveal that law enforcement has not yet achieved the expected level of effectiveness due to limited investigative resources, insufficient operational budgets, disharmonization of procedural regulations, low public participation, and cultural tolerance toward narcotics misuse. The gap between das sollen (normative law) and das sein (law in action) remains prominent. To enhance effectiveness, this study recommends strengthening institutional capacity, improving inter-agency coordination, optimizing investigative technology, and revitalizing legal awareness within communities.